2019
DOI: 10.1111/csp2.83
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term effects of energy development on winter distribution and residency of pronghorn in the Greater Yellowstone Ecosystem

Abstract: An increasing global demand for energy assures continued disturbance to previously undeveloped landscapes, but understanding broader impacts to wildlife remains elusive. Among groups of species most vulnerable to habitat disruption are those requiring large tracts of land. Pronghorn (Antilocapra americana) are an obligate to the open plains and basins that, similar to other transcontinental large herbivores, rely primarily on habitats where development of energy resources such as oil, natural gas, coal, wind, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 50 publications
(102 reference statements)
1
25
0
Order By: Relevance
“…For example, Green et al (2017) reported that between 1984 and 2008, there was a 2.5% annual reduction in lek attendance by sage grouse (Centrocercus urophasianus) as a result of oil and gas facilities being placed adjacent to lekking areas, providing evidence of population-level effects of energy development. Although the scientific literature is replete with retrospective analyses of effects of industrial activities to wildlife (Northrup and Wittemyer 2013, Green et al 2017, Sawyer et al 2019) many negative consequences resulting from human actions could have been prevented or reduced with sufficient pre-development planning.…”
mentioning
confidence: 99%
“…For example, Green et al (2017) reported that between 1984 and 2008, there was a 2.5% annual reduction in lek attendance by sage grouse (Centrocercus urophasianus) as a result of oil and gas facilities being placed adjacent to lekking areas, providing evidence of population-level effects of energy development. Although the scientific literature is replete with retrospective analyses of effects of industrial activities to wildlife (Northrup and Wittemyer 2013, Green et al 2017, Sawyer et al 2019) many negative consequences resulting from human actions could have been prevented or reduced with sufficient pre-development planning.…”
mentioning
confidence: 99%
“…Given deer are highly philopatric even in the presence of substantial development (Robinette 1966, Garrott et al 1987, Northrup et al 2016 b ), and our fidelity analysis exemplified this behavior in over 400 individuals in this study, we do not find evidence that deer are currently abandoning their winter ranges to a greater degree in the high‐development area. Sawyer et al (2006) and Sawyer et al (2019) found deer and pronghorn, respectively, to be strongly displaced at the onset of development. Thus, density differences could result from displacement of sensitive individuals before initiation of our study, or the emigration of juveniles, which we did not follow for multiple years.…”
Section: Discussionmentioning
confidence: 97%
“…Despite some behavioral responses, Beckmann et al (2016) found that pronghorn survival, mass, fecal corticosteroids, and progesterone were nearly identical between developed and undeveloped areas. However, Sawyer et al (2019), working on pronghorn over a 15-year period in an overlapping study area, documented an increase in the number of individuals abandoning their ranges, which complicates interpretation of the results of Beckmann et al (2012Beckmann et al ( , 2016. These congruent and contrasting findings across regions and species have implications for regulations aimed at reducing impacts of hydrocarbon development on wildlife.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations